Finite-difference time-domain simulation of THz light pulse with orbital angular momentum produced using a spiral phase plate - Alaba, Kenneth Jay; Bardolaza, Hannah; Hermosa, Nathaniel; Estacio, Elmer (Communications in Physics, 2024)
A silicon spiral phase plate was proposed for a pulsed terahertz beam to produce orbital angular momentum with a topological charge of \(l=1\). The resulting field distribution after the terahertz pulse traverses the silicon spiral phase plate was simulated using finite-difference time-domain method and was observed at different propagation distances. The simulation shows that a helical spatial structure and optical vortex can be observed in the pulse due to the silicon spiral phase plate and is best observed at the farthest distance of 7.5 cm. Additionally, the cross-section field distribution of the pulse at different times as it passes through the silicon spiral phase plate indicates a helical wavefront structure. Moreover, the output of a source beam with different central frequencies was observed when using the same silicon spiral phase plate where it similarly showed a hollow distribution, indicating a vortex albeit being located off-center. This demonstrates the generation of a structured beam with orbital angular momentum of electromagnetic waves using silicon spiral phase plate for a broadband terahertz single pulse.